ARL11 regulates lipopolysaccharide-stimulated macrophage activation by promoting mitogen-activated protein kinase (MAPK) signaling - Arya, Subhash B. (J Biol Chem, 2018)
ADP-ribosylation factor-like GTPase 11 (ARL11) is a cancer-predisposing gene that has remained functionally uncharacterized to date. In this study, we report that ARL11 is endogenously expressed in mouse and human macrophages and regulates their activation in response to lipopolysaccharide (LPS) stimulation. Accordingly, depletion of ARL11 impaired both LPS-stimulated pro-inflammatory cytokine production by macrophages and their ability to control intracellular replication of Salmonella. LPS-stimulated activation of extracellular signal–regulated kinase (ERK) and p38 mitogen-activated protein kinase (MAPK) was substantially compromised in Arl11-silenced macrophages. In contrast, increased expression of ARL11 led to constitutive ERK1/2 phosphorylation, resulting in macrophage exhaustion. Finally, we found that ARL11 forms a complex with phospho-ERK in macrophages within minutes of LPS stimulation. Taken together, our findings establish ARL11 as a novel regulator of ERK signaling in macrophages, required for macrophage activation and immune function.